Unveiling the Power of Pedagogically Productive Conversations Among University Teachers - Adeoye, Moses Adeleke; Akinnubi, Paul Olaolu; Makinde, Semiu Olawale; Ibrahim Solahudeen Owoyale-Abdulganiy; Abiola, Muhydeen Olaitan (Jurnal Pedagogi dan Pembelajaran, 2024)
The significance and benefits of discussion in higher education contexts have the potential to improve teaching practices, encourage professional development, and ultimately improve student learning outcomes. This study aims to analyze the potential impact of pedagogically productive conversations among university teachers. The research method uses Systematic Literature Review (SLR). A literature search was conducted through academic databases, such as PubMed, ERIC, and Google Scholar. Through a comprehensive review of relevant literature and firsthand insights from educators, the study delves into the intricacies of pedagogically productive conversations, emphasizing their role in promoting collaboration and creating a supportive academic environment. Furthermore, the paper discusses the challenges and barriers that may impede the implementation of such conversations and proposes strategies to overcome them. Overall, this position paper serves as a valuable resource for educators, administrators, and policymakers, offering insights into the transformative power of pedagogically productive conversations and advocating for their integration into the fabric of university teaching.